Effectiveness of Motor Imagery Training to Improve Gait Abilities of Patients with Sub-Acute Stroke - Sumreen Anwar, Muhammad Usman Fayyaz, Sumbal Saleem, Abdullah Imran, Hina Noman, Syed Saqib Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the effectiveness of motor imagery training to improve the lower extremity function and gait in subjects with sub-acute stroke. Methods: Forty four patients with subacute stroke with gait impairment were randomly assigned to one of two groups: motor imagery training group or muscle relaxation group. At the beginning and after six weeks of therapy, the ability to use motor imagery and lower limb performance were assessed. Results: There were substantial differences of scores between both groups, with the motor imagery group progressing more than the muscle relaxation group. Conclusion: Motor imagery may have a beneficial and effective task-specific effect on gait function in sub-acute stroke patients.